Unravelling the key aroma compounds in the characteristic fragrance of Dendrobium officinale flowers for potential industrial application. (August 2022) - Yang, Yu-Han; Zhao, Jie; Du, Zhi-Zhi
Abstract: Dendrobium officinale Kimura et Migo, one of the most important orchids because of its medicinal and edible value, has a typical Dendrobium Sw. flora scent, which has great application potential and commercial value to be characterized. The aroma-active compounds originating from D. officinale fresh flowers (DFF) were investigated using a sensomics approach. A combined solid phase microextraction and solvent-assisted flavor evaporation method were used to accurately capture the overall aromatic profile. Exactly 34 odorants were detected and identified by aroma extract dilution analysis (AEDA) coupled with gas chromatography/olfactometry−mass spectrometry (GC/O−MS) in DFF, of which nine odorants had a flavor dilution (FD) factor ≥27. All 34 odorants were further quantified. The odor activity values (OAVs) were calculated with the highest value of 7444, in which 18 compounds were confirmed to be key odorants, including 1-octen-3-ol, hexanal, nonanal, phenylacetaldehyde, linalool, 4-oxoisophorone, theaspirane, methyl salicylate, etc. Among the studies above, 42 out of 78 volatiles and 14 out of 34 odorants were identified in DFF for the first time. Then, the aroma profile of the DFF was simulated successfully by aroma recombination experiments based on the quantitation results, and the omission test suggested that alcohols are the decisive type of compounds in the DFF key odorants. In addition, a progressive addition test showed that the aroma recombinate prepared with 18 reference key odorants was able to reconstruct the characteristic aroma of DFF. In comparison, the recombinate constituted by mixing all 34 reference odorants in the same concentrations as determined in the DDF sample could mimic the flower scent and closely match the sensory attributes of the original D. officinale fresh flower. Graphical abstract: Image 1 Highlights: Solvent assisted flavor evaporation was used to extract the volatiles of Dendrobium officinale fresh flower (DFF). The key odorants of DFF were identified by sensomics approach. The nature scent of DFF was simulated successfully by aroma-recombination model. The simplest chemical formula of the characteristic aroma of DFF was established.